Natural resources, demand for external finance and financial development - Christian Hattendorff (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2014)
The paper contributes to the ongoing debate on the natural resource curse, which postulates a negative link between natural resource abundance and economic growth. It shows empirically that resource-rich countries appear to have a less developed financial system and investigates a potential mechanism behind this connection by applying insights from the finance and trade literature. It tests whether the resource sectors' lower demand for short-term external credit negatively affects financial development. This is done with cross-sectional and panel analysis, using an instrument for credit demand based on exogenous geographic determinants. The results, however, suggest that poor economic diversity rather than firms' credit demand drives the detrimental effect of resources on finance.
Keywords: F10; G10; O13; O16; 330; financial development; external dependence; natural resource curse; international trade; gravity model